No Power Over God’s Bounty: A Christian Commentary on the “People of Scripture” in the Qur’an, by Pim Valkenberg. - Sydnor, Jon Paul (Interreligious Studies and Intercultural Theology, 2022)
No Power Over God’s Bounty: A Christian Commentary on the “People of Scripture” in the Qur’an, by Pim Valkenberg. Paris: Peeters, 2021. xv + 444 pages. $103 US. Series: Christian Commentaries on Non-Christian Sacred Texts. ISBN 978 9042941779